Searching for chromospheric activity cycles in 1111 FGK-type stars from the HARPS GTO planet search program - Flores, M. (2019)
The monitoring of many stars with magnetic cycles could help for a better understanding of their dependence with the stellar properties and the place occupied by the Sun in this context. Up to now, there are many questions related with the solar cycle (for example, amplitude, shape and length cycle fluctuations), which could be addressed if the number of stellar activity cycles detected in solar-analogues and solar-twin stars were increased. In this work, we performed a systematic search for chromospheric activity cycles in a sample of 1111 FGK stars belonging to the HARPS GTO planet search program. As a result, we were able to analyse in detail the chromospheric activity for 600 of these objects. To this end, we calculate the Mount Wilson index for each object and then the corresponding temporal series were individually analysed by using the generalised Lomb-Scargle periodogram.